2005
DOI: 10.1074/jbc.m411673200
|View full text |Cite
|
Sign up to set email alerts
|

Licorice Compounds Glycyrrhizin and 18β-Glycyrrhetinic Acid Are Potent Modulators of Bile Acid-induced Cytotoxicity in Rat Hepatocytes

Abstract: The accumulation of hydrophobic bile acids results in cholestatic liver injury by increasing oxidative stress, mitochondrial dysfunction, and activation of cell signaling pathways. Licorice root and its constituents have been utilized as antihepatotoxic agents. The purpose of this study was to evaluate the potential modulation by a primary component of licorice root, glycyrrhizin (GL), and its metabolite, 18␤-glycyrrhetinic acid (GA), in a hepatocyte model of cholestatic liver injury. Preincubation of fresh ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(88 citation statements)
references
References 55 publications
5
78
3
Order By: Relevance
“…37) Taken together, these results suggested an important role of MAPKs in the regulation of apoptosis during liver I/R. Previous study has shown that CT protected primary cultured rat hepatocytes from bile acid-induced apoptosis by inhibiting JNK phosphorylation.…”
Section: Discussionsupporting
confidence: 53%
“…37) Taken together, these results suggested an important role of MAPKs in the regulation of apoptosis during liver I/R. Previous study has shown that CT protected primary cultured rat hepatocytes from bile acid-induced apoptosis by inhibiting JNK phosphorylation.…”
Section: Discussionsupporting
confidence: 53%
“…Gc has been used against chronic viral hepatitis [21] and is reportedly active against a number of other viruses, including latent Kaposi sarcoma-associated herpes virus [22], severe acute respiratory distress syndrome (SARS) [23,24], and EpsteinBarr Virus (EBV) (Lin, 2008 #307). It was reported to exert protection against carbon tetrachloride-induced liver injury in mice [25], liver damage associated with aflatoxin-induced oxidative stress [26] and other types of liver damage induced by oxidative stress [27]. These licorice compounds also can induce interferon production [26,28] and protect against neurotoxicity by modulating the binding of nuclear factorkappaB to its molecular targets [29].…”
Section: Glycyrrhizin and Glycyrrhetic Acidmentioning
confidence: 99%
“…Additionally, GA and GL had antagonistic effects toward GCDC-induced cytotoxicity; GL enhanced apoptosis whereas GA prevented both necrosis and apoptosis. 9 GA effect on the subcutaneous fat thickness was performed through topically applied cream containing GA, results in reduction of unwanted local fat accumulation. It was found to be due to the blockage of 11β-hydroxysteroid dehydrogenase type 1 at the level of fat cells.…”
Section: Introductionmentioning
confidence: 99%